Pelatihan Dasar dan Aplikasi Internet of Things di Sekolah Menengah Atas Negeri 6 Metro Lampung - Mege, Christio Revano; Suaif, Ahmad; Putra, Septia Eka Marsha; Khoirunisa, Vera; Siregar, Sefrani IG; Saputra, Alvin; Ramadhani, Sofia Nur (Yayasan Sumber Daya Manusia Cerdas, 2025)
Metro 6 State Senior High School is one of the schools that produces the best graduates in Metro City. Learning at this school strives to utilize the latest technology that is in accordance with the needs of the times. One technology that has not been taught at this school is Internet of Things technology. The Internet of Things (IoT) is a concept that refers to a network of physical devices connected via the internet, which are able to exchange data without requiring human-to-human or human-to-computer interaction. In the context of IoT,